The leverage ratio, risk-taking and bank stability - Jonathan Acosta Smith; Michael Grill; Jan Hannes Lang (European Central Bank (ECB), 2017)
This paper addresses the trade-off between additional loss-absorbing capacity and potentially higher bank risk-taking associated with the introduction of the Basel III Leverage Ratio. This is addressed in both a theoretical and empirical setting. Using a theoretical micro model, we show that a leverage ratio requirement can incentivise banks that are bound by it to increase their risk-taking. This increase in risk-taking however, should be more than outweighed by the benefits of higher capital and therefore increased lossabsorbing capacity, thereby leading to more stable banks. These theoretical predictions are tested and confirmed in an empirical analysis on a large sample of EU banks. Our baseline empirical model suggests that a leverage ratio requirement would lead to a significant decline in the distress probability of highly leveraged banks.
Keywords: G01; G21; G28; 330; Bank capital; Risk-taking; Leverage ratio; Basel III